PENGARUH ORGANIZATION EMPLOYEE RELATIONSHIP TERHADAP ORGANIZATIONAL RESILIENCE - Aji Samba Pranata Citra; Maya Rosmayati Ardiwinata; Anissa Lestari Kadiyono (BBM (Buletin Bisnis & Manajemen), 2021)
The purpose of this study was to see the effect of Organizational Employee Relationship onOrganizational Resilience Hotel X in facing a crisis. Every crisis creates a lot of uncertainty for allmembers of the organization, including employees. The focus of this research is to see thedynamics of the relationship between employees and their organizations in dealing with crisesbetter in order to remain resilient during and after the crisis. The sample in this study was n = 48employees of hotel X which were selected by simple random sampling. The results obtained showthat there is an influence of Organizational Employee Resilience on Organizational Resilience.